THE CORRELATION BETWEEN EIGHTH GRADERS’ LEARNING MOTIVATION AND ENGLISH ACHIEVEMENT DURING THE PANDEMIC AT SMPN 1 TARAKAN - Oktafiani, Megawati; Eppendi, Jhoni (Borneo Journal of English Language Education, 2023)
This study investigated the association between students' enthusiasm to learn and their English academic performance in the eighth grade at SMPN 1 Tarakan during the pandemic. This investigation employed a quantitative methodology based on the correlation method. A stratified random sampling procedure was used to choose the 54 eighth-graders from SMP Negeri 1 Tarakan sample. A learning motivation survey and an examination of the student's English Semester Exam results were used to gather the data. The association between students' motivation for learning and their proficiency in English was examined using Pearson's product-moment correlation. The mean score of 59.50 out of 29.63% on the questionnaire indicated that the eighth graders of SMPN 1 Tarakan were not enthusiastic about learning despite the epidemic. During the pandemic, the English scores of eighth-graders were also low, with a mean score of 57.19, or approximately 66.67%. During the pandemic, students at SMPN 1 Tarakan exhibited a highly significant correlation between their English achievement and their motivation to learn, as indicated by this finding.